Investigating the Strategies Used in Translation of Ironies in English Short Stories translated into Persian - Mana Alahmad (BIRCU, 2019)
This study attempted to investigate the strategies which were used by Persian translators in translation of ironies. Translating irony has always been challenging as it relates to each nation culture and language background. So, special strategies are needed to guide the translators to find suitable equivalences for the ironies within any second language. In this research, strategies for translating two types of ironies i.e. verbal and situational were investigated via short stories. Eight short stories of Ernest Hemingway were chosen as the English texts. For each story two Persian versions were selected.Baker (1992) model of translation strategies was considered as the framework. The result of the total frequency count of the strategies adopted in translating the ironies by the translators’indicated that the most common strategies which used by these translators to translate English verbal and situational ironies into Persian were cultural equivalences and general or neutral equivalences for English words and phrases.The findings are of help to translators, translation trainers and readers among all interested parties